(untitled) (Scientific journal of the Fergana State University, 2023)
This article describes the policy of repression, carried out in the 40s and 50s of the 20th century, and its impact on the spiritual life of the population. In particular, according to the sources, the negative impact of the policy of this period on the religious, cultural, personnel, scientific spheres of life of the population was studied. In addition, the article highlighted the rules established by the Soviet government, and the penalties applied to those who did not comply with them, as well as the fact that people who feared falling into the punitive machine of the former union were separated from their national values and identity during this period. In the conclusion of the article, it is noted that the independence of Uzbekistan is the highest blessing bestowed on the Uzbek people, the restoration of historical facts and justice, the formation of the spiritual thinking of the people is the key to the development of the country.